Pengaturan Investasi Dalam Pengembangan Perdagangan Jasa Pariwisata Usia Lanjut - Ida Bagus Bayu Brahmantya (Jurnal Ilmiah Raad Kertha, 2018)
Age rating is diverse, retirement market or seniors market is important because of the large group market and its potential to growth. Retirement travelers is stable in terms of financial reserves, so they tend to be free of economic pressures. UU No. 10 of 2009 does not regulate tourism as a form of trade in services, because not all activities related to tourism is tourism. Only a sightseeing trip with all aspects of the supply of certain services in it. Certain services in question are transport services, accommodation, catering services, information services, services of travel documents, schedule maintenance services and travel destinations, financial services, services, attractions, and other specific services are an aspect of tourism. The supply of tourism services for elderly travelers is already there and walked in Indonesia. However, processes and systems that are used at this time has not been able to maximize the utilization of tourist markets such great longevity. Tourism policies imposed against the retirement is still general and relies on tourism policy that applies to the travel, hospitality, catering services, and so forth, so that less attention to the special nature and special needs of the elderly tourism.Based on these descriptions, it is relevant to do with the problems of the scientific studies how trade investment arrangements retirement tourism services that are applicable today? and how construction investment arrangements in the development of trade in tourism for the retirement in accordance with the characteristics of the retirement rating? The problems that arise can be seen that this research is a type of normative legal research using the approach of legislation and approach to the concept.